Dual malignancies: a case report of the sequential occurrence of a trichilemmal tumor and breast carcinoma in a 56-year-old female - Vuppumalla, Bhargav; Ravichandran, A.; Manickavasagam, M.; Javvaji, Chaitanya Kumar; Vagha, Keta (Frontiers in Oncology, 2025)
The authors present a rare case of the sequential occurrence of a malignant trichilemmal tumor (MPTT) and invasive ductal carcinoma of the breast in a 56-year-old woman. The patient initially presented with a palpable breast lump and a longstanding asymptomatic scalp swelling that had been present since childhood. Histopathological evaluation confirmed the breast lump as invasive ductal carcinoma, while the scalp swelling, initially suspected to be a benign cyst, was diagnosed as an MPTT. The patient underwent combination chemotherapy, which resulted in a favorable response of the breast carcinoma; however, the MPTT exhibited a discordant therapeutic outcome. Trichilemmal carcinoma is an uncommon cutaneous neoplasm, and its coexistence with breast carcinoma represents an exceedingly rare clinical scenario. Furthermore, the differential response of these malignancies to chemotherapy presents a significant therapeutic challenge. This case underscores the importance of accurate diagnosis, individualized treatment strategies, and a multidisciplinary approach for optimally managing such complex oncological presentations.